2023
DOI: 10.1039/d2py01601j
|View full text |Cite
|
Sign up to set email alerts
|

New long-wavelength D–π-A–π-D chalcone photoinitiator for visible light polymerization with photobleaching and biocompatibility properties

Abstract: Four chalcones with large conjugated structures have been designed and synthesized. The excellent absorption properties of four chalcones in the visible region (λmax = 407 ~ 483 nm, εmax =...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The experimental results were also consistent with our previous work. 27 The above results suggested that there could be charge transfer and redox reactions between photo-excited bis-chalcone and Iod, resulting in changes in absorption spectra.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…The experimental results were also consistent with our previous work. 27 The above results suggested that there could be charge transfer and redox reactions between photo-excited bis-chalcone and Iod, resulting in changes in absorption spectra.…”
Section: Resultsmentioning
confidence: 86%
“…The experimental results were also consistent with our previous work. 27 The above results suggested that there could be charge transfer and redox reactions between photo-excited bis-chalcone and Iod, resulting in changes in absorption spectra. For visible light photoinitiators, their color was often very deep due to their absorption in the visible light region.…”
Section: Photosteady-state Degradation and Photobleachingmentioning
confidence: 86%
See 1 more Smart Citation
“…For Type II photoinitiators systems, chalcone-based compound was classified as a promising hydrogen acceptor photoinitiator due to the facile synthetic procedures and long absorption wavelengths. [19][20][21] For further boarding the light absorption regions of the chalcone, different chromophores such as triphenylamine, [22][23][24] carbazole, [22,25] phenothiazine, [26] aromatic ring, [27,28] heterocyclic structures [29] had been introduced by the researchers. Furthermore, symmetrical bis-chalcones combine two chromophores extended conjugation length more significantly, which were beneficial for the light harvesting.…”
Section: Introductionmentioning
confidence: 99%
“…If this approach is of interest, photons of the visible spectrum exhibit lower energy than UV photons so that visible light photoinitiating systems of higher reactivity should be designed in order to compensate for this reduction of energy. To address this issue, a wide range of structures have been explored as exemplified by camphorquinone [29,30], thiophenes [31], push-pull dyes [2,32,33], anthracenes [34], acridine-1,8-diones [35], benzylidene ketones [36][37][38][39][40][41], chromones and flavones [42][43][44], perylenes [45], diketopyrrolopyrroles [46,47], naphthalimides [48][49][50][51][52][53][54], cyclohexanones [55][56][57][58], chalcones [24,[59][60][61][62][63][64], dithienophosphole derivatives [65], thioxanthones [66][67][68][69][70][71][72...…”
Section: Introductionmentioning
confidence: 99%